2017
DOI: 10.1038/s41467-017-01329-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of telomere protection by the PI3K/AKT pathway

Abstract: Telomeres and the insulin/PI3K pathway are considered hallmarks of aging and cancer. Here, we describe a role for PI3K/AKT in the regulation of TRF1, an essential component of the shelterin complex. PI3K and AKT chemical inhibitors reduce TRF1 telomeric foci and lead to increased telomeric DNA damage and fragility. We identify the PI3Kα isoform as responsible for this TRF1 inhibition. TRF1 is phosphorylated at different residues by AKT and these modifications regulate TRF1 protein stability and TRF1 binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…Similarly, TRF1 is known to interact with Akt, a ubiquitous serine threonine protein kinase involved in metabolism and growth factor signaling. Indeed, PI3Kα, a downstream target of Akt, has been recently identified to regulate TRF1 protein expression . Further studies elucidating these potential shelterin regulators may allow for small molecule compounds which may help improve shelterin function, reduce senescence in old arteries or CVDs thereby improving function.…”
Section: Prospective: Targeting Shelterin As a Novel Anti‐aging Strategymentioning
confidence: 99%
“…Similarly, TRF1 is known to interact with Akt, a ubiquitous serine threonine protein kinase involved in metabolism and growth factor signaling. Indeed, PI3Kα, a downstream target of Akt, has been recently identified to regulate TRF1 protein expression . Further studies elucidating these potential shelterin regulators may allow for small molecule compounds which may help improve shelterin function, reduce senescence in old arteries or CVDs thereby improving function.…”
Section: Prospective: Targeting Shelterin As a Novel Anti‐aging Strategymentioning
confidence: 99%
“…Next, we set to study the mechanisms by which the newly identified compounds regulate TRF1 levels. We had previously reported that the TRF1 telomeric protein is regulated by the PI3K signaling pathway (Mendez‐Pertuz et al , ). In particular, TRF1 is directly phosphorylated by the PI3K downstream target AKT at different residues (T248, T330, and S344), and this phosphorylation is necessary for TRF1 stability and TRF1 foci formation in vivo (Mendez‐Pertuz et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we demonstrate that, among the AKT‐dependent phosphosites of TRF1, S344 (T358 in human) is as also a target for ERK‐mediated phosphorylation (Fig O). As negative control, we also generated a TRF1 phosphomutant in residue T248 whose phosphorylation is mediated by AKT but not ERK (Fig O; Mendez‐Pertuz et al , ). As expected, this mutant did not result in decreased TRF1 phosphorylation (Fig O).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations